It Takes a Village: Bridging the Gaps between Current and Formal Specifications for Protocols. - Basin, David; Foster, Nate; McMillan, Kenneth L.; Namjoshi, Kedar S.; Nita-Rotaru, Cristina; Smith, Jonathan M.; Zave, Pamela; Zuck, Lenore D. (Communications of the ACM, 2025)
This article focuses on the current lack of use of formal methods (FM) for network protocols and what can be done to overcome challenges and implement FM for networking communities. Specification in networking communities is a focus as well as examples of successful FM use in real-world protocols, including transport layer security and Quick UPD Internet Connection. Lastly, the authors present solutions to this gap which include integration of FM in computer science education and integration of design and verification.